Study on the prevalence of dyslipidemia in type 2 diabetes mellitus - Dayakar, Eda; Sree, C. Sathya; Sanjay, E. (International Journal of Advances in Medicine, 2019)
Background: Diabetes mellitus is a common health problem globally. Dyslipidaemia is a major risk factor to develop cardiovascular disease in diabetics. They present study was undertaken to find out the prevalence of dyslipidaemia in type 2 diabetic patients. Methods: The present study was a cross sectional study consisting of 46 (23 male and 23 female) known type 2 diabetes mellitus patients. Age, gender, duration of diabetes, body mass index (BMI) was recorder in all the diabetic patients. Fasting blood glucose levels, total cholesterol, triglycerides, HDL, LDL, VLDL levels were measured using standard methods and recorded. Results: The average total cholesterol, triglycerides, LDL, HDL and VLDL were 200±42mg/dl, 169.62±89.79mg/dl, 132.45±36.38mg/dl,39.1±16.6mg/dl and 35.85±17.09mg/dl respectively. The incidence of occurrence of hypercholesterolemia was 58.6% and hypertriglyceridemia 36.9%. Increased levels of LDL were observed in 30 (65.2%) patients and reduced HDL was observed in 43 (93.4%) patients. The incidence rate of dyslipidaemia was higher in female diabetic patients when compared to male diabetic patients. Conclusions: Awareness on the dyslipidaemia and its risk factors should be provided to the type 2 diabetic patients as they are more prone to get cardiovascular disease and lipid profile also should be monitored regularly along with blood glucose levels.